Behavior of Concrete-Filled Steel Tube Columns Subjected to Axial Compression. (26th August 2018) - Li, Pengfei; Zhang, Tao; Wang, Chengzhi
Abstract : The behavior of concrete-filled steel tube (CFST) columns subjected to axial compression was experimentally investigated in this paper. Two kinds of columns, including CFST columns with foundation and columns without foundation, were tested. Columns of pure concrete and concrete with reinforcing bars as well as two steel tube thicknesses were considered. The experimental results showed that the CFST column with reinforcing bars has a higher bearing capacity, more effective plastic behavior, and greater toughness, and the elastoplastic boundary point occurs when the load is approximately 0.4–0.5 times of the ultimate bearing capacity. The change of rock-socketed depth and the presence of steel tube will affect the ultimate bearing capacity of rock-socketed pile. The bearing capacities of the rock-socketed CFST columns are lower than those of rock-socketed columns without a steel tube under a vertical load; besides, the greater the rock-socketed depth, the greater the bearing capacity of the rock-socketed piles. In addition, a numerical comparison between the ultimate load and the theoretical value calculated from the relevant specifications shows that the ultimate load is generally considerably greater than the theoretical calculation results.